Initial screening of mangrove endophytic fungi for antimicrobial compounds and heavy metal biosorption potential - Onn, M. Ling; Lim, Po Teen; Aazani, Mujahid; Proksch, Peter; Müller, Moritz (Universiti Kebangsaan Malaysia, 2016)
Endophytic fungi provide protection to their host plant and the fungi often produce antimicrobial compounds to aid the host fighting off pathogens. These bioactive compounds were secondary metabolites which were often produced as waste- or by-products. In the present study, endophytic fungi isolated from mangrove plants and soils were characterized and their antimicrobial production and bioremediation potential of heavy metals copper (Cu) and zinc (Zn) were assessed. Twelve (12) isolated and identified endophytic fungi belonged to seven species; Penicillium, Curvularia, Diaporthe, Aspergillus, Guignardia, Neusartorya and Eupenicillium. Antimicrobial activities of these 12 fungal endophytes were tested against Gram negative bacteria; Bacillus subtilis, Staphylococcus aureus, Gram positive bacteria; Escherichia coli and fungi; Candida albicans and Aspergillus Niger among others. Two isolates (related to Guignardia sp. and Neusartoya sp.) showed strong antimicrobial (and antifungal) activity whereas the rest showed no activity. Compounds were isolated from both isolates and screened using HPLC. Both isolates displayed chemically very interesting chromatograms as they possessed a high diversity of basic chemical structures and peaks over a wide range of polarities, with structures similar to Trimeric catechin and Helenalin among others. For bioremediation assessment, the results showed maximum biosorption capacity for two isolates related to Curvularia sp. and Neusartorya sp., with the former removing 25 mg Cu/g biomass and the latter removing 24 mg Zn/g biomass. Our results indicated the potential of mangrove endophytic fungi in producing bioactive compounds and also highlighted their potential for the treatment of heavy metal-contaminated wastewater